2011
DOI: 10.1590/s0104-11692011000300021
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and work capacity of nurses of a hospital group

Abstract: The study aimed to evaluate the relationship between occupational stress and the work capacity index of 368 nurses (82.1% of the population) of a Hospital Group. A questionnaire with socio-occupational questions was used as well as two scales: the Job Stress Scale and the Work Capacity Index. The group of nurses was predominantly female (93.2%), worked in care activities (63.9%), had undertaken at least one Postgraduate course (76%) and were satisfied with the unit where they worked (70.5% Estrés laboral y ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
4
18
2
9
Order By: Relevance
“…In this case, such demands may influence the work ability of the professionals. However, the association found in this study differs from results shown in other studies: one (12) , conducted in a public hospital in São Paulo with the nursing staff, and another (9) , with nurses in a hospital group in Porto Alegre/Rio Grande do Sul, showed no statistically significant association between high-strain and reduced nursing work ability.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this case, such demands may influence the work ability of the professionals. However, the association found in this study differs from results shown in other studies: one (12) , conducted in a public hospital in São Paulo with the nursing staff, and another (9) , with nurses in a hospital group in Porto Alegre/Rio Grande do Sul, showed no statistically significant association between high-strain and reduced nursing work ability.…”
Section: Discussioncontrasting
confidence: 99%
“…Of these, one (10) , developed with workers from a bus transportation company, showed a positive association between stress and a reduction in the work ability. The other (9) , with nursing staff, showed no association in this relationship.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Portanto, quanto maior a compreensão e o controle das situações e pressões no ambiente laboral, melhor será sua adaptação e, consequentemente, menor o indicativo de estresse (20) .…”
Section: Discussionunclassified
“…Esses autores descreveram adicionalmente a falta de autonomia e o excesso de trabalho como aumento das situações de risco. 23 Como principal limitação do estudo identifica-se o fato de que as notificações foram passivas, portanto, assistemáticas, o que pressupõe a subnotificação. Dessa maneira, há probabilidade de que o número de incidentes seja maior.…”
Section: Agradecimentosunclassified